PARAMETRIC AND NON-PARAMETRIC METHODS TO EVALUATE WINTER RYE GENOTYPES BY GRAIN YIELD STABILITY - Desheva, GERGANA; Valchinova, Evgeniya; Pencheva, Albena (Journal of Agricultural Sciences (Belgrade), 2025)
The aim of this study was to identify high-yielding, stable and adaptive rye landraces and cultivars for commercial and breeding purposes. The trial was carried out from 2014 to 2022 and included 16 cultivars and 7 Bulgarian landraces. The experiment was conducted in a block design with randomized design of the variants in four replications. Sixteen parametric and non-parametric parameters of grain yield stability were determined. The average of the sum ranks (ASR), the AMMI stability value (ASV), the yield stability index (YSI) and the genotype selection index (GSI) were also calculated. Year had the highest statistically significant effect on the grain yield per hectare. Parametric and non-parametric stability parameters estimated G13, G12, G20 and G21 genotypes as the most stable. ASV identified G13, G18, G12 and G9 as the most stable genotypes, while YSI found G13, G19, G12 and G18, respectively. GSI classified G13, G12, G18, and G19 as genotypes with the broadest adaptability to adverse climatic conditions. They could serve as source material in rye breeding programmes.
Keywords: rye, yield, stability analysis, adaptability